Completeness of BPJS Kesehatan Outpatient Claims at RSD Idaman Banjarbaru - Siti Tanzilah; Melinda Restu Pertiwi (Salando Health Journal, 2026)
Background: The completeness of BPJS Kesehatan outpatient claims is essential for hospital claims management under the National Health Insurance (JKN) Program. Incomplete administrative requirements, diagnosis and procedure codes, and medical documentation may contribute to pending claims and delayed reimbursement. This study aimed to describe the completeness of BPJS Kesehatan outpatient claims at RSD Idaman Banjarbaru based on these components. Methods: This quantitative study used a retrospective descriptive design at the JKN Unit of RSD Idaman Banjarbaru from July to September 2025. The population consisted of 386 pending outpatient claim files, with 196 selected using the Slovin formula and purposive sampling. Data were collected using a structured checklist and analyzed using univariate analysis, presented as frequencies and percentages. Patient confidentiality and anonymity were maintained. Results: Of 196 pending claim files, 167 (85.2%) had complete administrative requirements and 29 (14.8%) were incomplete. Complete diagnosis and procedure codes were found in 71 files (36.2%), while 125 (63.8%) were incomplete. Complete medical documentation was found in 176 files (89.8%), while 20 (10.2%) were incomplete. Common deficiencies included missing control and referral letters, incomplete diagnosis and procedure codes, and incomplete supporting medical documentation. Conclusion: Claim completeness differed across components. Incomplete diagnosis and procedure codes were the most frequent deficiency, followed by administrative requirements and medical documentation. Improving claim document completeness is important to support effective hospital claims management.